2022
DOI: 10.1051/0004-6361/202243556
|View full text |Cite
|
Sign up to set email alerts
|

Stellar collisions in globular clusters: Constraints on the initial mass function of the first generation of stars

Abstract: Globular clusters display an anticorrelation between the fraction of the first generation of stars (N(G1)/N(tot)) and the slope of the present-day mass function of the clusters (α pd ), which is particularly significant for massive clusters. In the framework of the binarymediated collision scenario for the formation of the second-generation stars in globular clusters, we test the effect of a varying stellar initial mass function (IMF) of the G1 stars on the (N(G1)/N(tot)) −α pd anticorrelation. We use a simple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…This result has been predicted by Dib & Basu (2018) who attributed it to the existence of cluster-to-cluster variations of the IMF in Galactic clusters (see also Dib 2022). Variations of the IMF between galaxies have also been reported (Gunawardhana et al 2011;Geha et al 2013;Martín-Navarro et al 2015;Gennaro et al 2018), and these have been successfully interpreted as being due to variations in the average galactic gas-phase metallicity and SFR, and to the existence of various levels of IMF variations in their population of clusters (Yan et al 2017;Jerábková et al 2018;Dib et al 2022).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…This result has been predicted by Dib & Basu (2018) who attributed it to the existence of cluster-to-cluster variations of the IMF in Galactic clusters (see also Dib 2022). Variations of the IMF between galaxies have also been reported (Gunawardhana et al 2011;Geha et al 2013;Martín-Navarro et al 2015;Gennaro et al 2018), and these have been successfully interpreted as being due to variations in the average galactic gas-phase metallicity and SFR, and to the existence of various levels of IMF variations in their population of clusters (Yan et al 2017;Jerábková et al 2018;Dib et al 2022).…”
Section: Introductionsupporting
confidence: 57%
“…As Guszejnov et al (2019) stated, either the present-day mass function of these galaxies is problematic or the universality of the IMF in clusters is in question. Along this same idea, Dib & Basu (2018) and Dib et al (2022) showed how the presence of significant cluster-tocluster of the IMF can generate a bottom-heavy mass function in elliptical galaxies. Additionally, Dib et al (2022) showed that accounting for IMF variations in clusters coupled with a metallicity dependence of the IMF can help reproduce the galaxy-wide IMF of ultrafaint dwarf galaxies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Initial mass function (IMF) describes the mass distribution of stars that form together at the birth time. It is a crucial parameter in astrophysics (Dib et al 2022), influencing most observable properties of star clusters and galaxies. The IMF serves as a critical input parameter for theoretical models or for deriving other physical parameters based on observations (Romano et al 2005;Gu et al 2022).…”
Section: Introductionmentioning
confidence: 99%